Characterization and biological activity of condensed tannins from tropical forage legumes - Pereira, Tatiana Pires; Modesto, Elisa Cristina; Nepomuceno, Delci de Deus; Oliveira, Osniel Faria de; Freitas, Rafaela Scalise Xavier de; Muir, James Pierre; Dubex Junior, José Batista; Almeida, João Carlos de Carvalho (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to characterize condensed tannins (CT) from six tropical forage legumes and to determine their biological activity. The monomers propelargonidin, prodelphinidin and procyanidin were analyzed, as well as extractable condensed tannin (ECT), protein-bound CT (PBCT) and fiber-bound CT (FBCT), molecular weight, degree of polymerization, polydispersity index, and biological activity by protein precipitate by phenols (PPP) of leaves of the legumes Cajanus cajan, Gliricidia sepium, Stylosanthes capitata x Stylosanthes macrocephala (stylo), Flemingia macrophylla, Cratylia argentea, and Mimosa caesalpiniifolia, and of the bark of this latter species. Differences were observed in the concentrations of ECT, PBCT, PPP, and total condensed tannin among species, but not in that of FBCT. The highest value of PBCT occurred in F. macrophylla. Total CT varied from nondetected concentration in C. argentea to the highest concentration in M. caesalpiniifolia leaves that contain the greatest levels of PPP. No differences were observed for polymerization degree in stylo, F. macrophylla, and M. caesalpiniifolia. Leaves of stylo, C. cajan, and G. sepium, all containing between 20 and 50 g kg-1 total CT, should be beneficial CT sources, if offered as sole feeds in ruminant diets. The ratio of prodelphinidin:procyanidin varies from 10:80 (stylo) to 65:35 (F. machrophylla), and propelargonidin is only determined in C. argentea.
Keywords: forage legumes; phenols; procyanidins; prodelphinidins; protein